Carbonized Dehydroascorbic Acid: Aim for Targeted Repair of Graphene Defects and Bridge Connection of Graphene Sheets with Small Size - Jing Li; Jinfeng Lai; Jialiang Liu; Rubai Lei; Yuxun Chen (Nanomaterials, 2020)
The thermal dissipation issue of electronics devices becomes increasingly prominent as they evolve to smaller sizes and more complicated structures. Therefore, the development of materials with excellent heat conduction properties and light weight turns out to be an urgent demand to solve the heat transfer problem of electronics devices with high performance. For this purpose, we put forward an innovative strategy that carbonized dehydroascorbic acid (CDA) be applied to graphene layers for the targeted repair of defects among them and bridge connection of the layers to produce graphene heat conduction materials with excellent properties. Firstly, hydrogen bonds formed from dehydroascorbic acid (DHAA, products of the oxidation of vitamin C) and each of ketone, carboxyl, and oxhydryl groups on graphene layers were absorbed at targeted locations where oxidation graphene produces defects, then targeted repair was conducted for those defects to be filled and for the graphene layers of a small size to grow into large sheet materials with improved continuity by CDA generated in thermally pressing reduction reaction at 800 °C. In our investigation, the planar thermal conductivity of rGO/VC membrane reached 1031.9 ± 10.2 Wm−1K−1, while the added mass content of vitamin C (VC) was 15%. Being a reference, the planar thermal conductivity of primitive graphene membrane was only 610.7 ± 11.7 Wm−1K−1.